2023
DOI: 10.3390/su151410824
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Integration of Cultural Tourism Industry Affect Rural Revitalization? The Mediating Effect of New Urbanization

Linqing Fang,
Zhihao Liu,
Caiyu Jin

Abstract: The development and integration of industries have promoted economic growth and gradually become an important perspective to understand the country’s modernized construction. The cultural industry and the tourism industry are naturally coupled, which is an important part of the process of industrial integration. In addition, the country’s drive towards modernization needs to improve the overall level of industrial integration, and rural revitalization is one of the key links to this. Therefore, to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…U c and U t are the comprehensive evaluation values for the culture industry and tourism industry, respectively, as calculated by the entropy method. Based on the existing studies [50,[63][64][65], this paper constructs the evaluation index system of these two industries from the two dimensions of industrial factors and industrial performance, covering a total of eight tertiary indicators, as shown in Table 2. ).…”
Section: Evaluation System Of the Integration Level Of The Culture In...mentioning
confidence: 99%
“…U c and U t are the comprehensive evaluation values for the culture industry and tourism industry, respectively, as calculated by the entropy method. Based on the existing studies [50,[63][64][65], this paper constructs the evaluation index system of these two industries from the two dimensions of industrial factors and industrial performance, covering a total of eight tertiary indicators, as shown in Table 2. ).…”
Section: Evaluation System Of the Integration Level Of The Culture In...mentioning
confidence: 99%
“…Second, horizontal path: agricultural multifunctionality expansion. This model centers on a single agricultural economic function, expands agricultural multifunctionality such as culture, ecology, tourism, education, etc., and forms a new industrial form dominated by leisure agriculture and rural tourism industry, which helps to keep the tertiary value derived from agriculture still in agriculture and reduce regional inequality [ 38 , 39 ]. Fiscal agricultural expenditures often take a variety of ways to support the integration of agriculture and rural tourism, for example, to build first and then subsidize, award in lieu of subsidy, work in lieu of relief, and other ways to help rural tourism develop, and gradually improve the rural roads, car parks, water and electricity supply, network, and other supporting facilities for agricultural life.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…To rectify this scenario, numerous nations, including Europe, Japan, and China, have progressively underscored the significance of rural development and initiated a succession of rural revitalization initiatives [7]. Academic research has extensively focused on rural revitalization, including in the areas of rural planning (Wang et al [8]), the preservation of traditional villages (Li et al [9]), and rural tourism (Fang et al [10]).…”
Section: Introductionmentioning
confidence: 99%